Quality Evolution and Aroma Profile of Pointed Cabbage in Different Storage Regimes - Janssens, Maxime; Verlinden, Bert E.; Hertog, Maarten L. A. T. M.; Nicolaï, Bart M. (Frontiers in Plant Science, 2022)
With its increasing popularity, the need for optimal storage conditions of pointed cabbages becomes more important to meet the year-round demand. Storage of the pointed varieties however, is more difficult compared to the traditional, round varieties and is limited to a few weeks in normal air. Pointed cabbages are more susceptible to quality loss (shriveling, yellowing of leaves, weight loss, fungal and bacterial infections) and tend to spoil much faster. In order to provide a year-round availability of the fresh product, storage under controlled atmosphere (CA) could offer a solution. In this study, pointed, white cabbage heads (Brassica oleracea var. capitata for. alba L. subv. Conica cv. ‘Caraflex’) were stored at 1 °C from November 2018 to May 2019 under four different CA conditions (1 kPa O2 + 1.5 kPa CO2, 1 kPa O2 + 5 kPa CO2, 3 kPa O2 + 1.5 kPa CO2, 3 kPa O2 + 5 kPa CO2), and compared to storage under normal air. Results showed that CA storage resulted in a prolonged storage life with a good quality retention for both texture and aroma. CA-stored cabbages showed less weight loss, shriveling and yellowing. Internal quality parameters (color, SSC) were stable over the whole storage period for all objects. The aroma profiles of both the storage atmosphere and cabbage samples were impacted by storage duration. The aroma of cabbage juice was also affected by the storage regime. A clear separation was found for cabbage stored under CA compared to the reference group. From the CA-treatments studied, a combination of low oxygen (1 kPa O2) and elevated carbon dioxide levels (5 kPa CO2) showed the best results maintaining quality. Storage under CA resulted in a better resemblance to the aroma of freshly, harvested produce compared to cabbages stored in normal air.